A efetividade das políticas públicas para a população afro-brasileira na cidade de São Paulo: uma “segunda abolição” sob o enfoque da Constituição Federal de 1988 - Nobre, Jadilson Vigas (2019)
The formation of our country had been made with black sweat and blood, marked out by persistent inequality. Throughout this work, we have been able to identify that the cause for racial exclusion occurs through the various forms of manifestation of racism, be it in the field of health, education of labor, as well as in general in social circles. We firmly believe in a change, although it should not occur in a short space of time. Several public policies are already in place and we want to believe that they have not yet been enough to reduce social ills in relation to the black people. We identified that the health of the black population still requires greater care, especially the black woman, in their reproductive health, resulting in a high mortality rate. We could also observe that racial quotas, although in a growth scale, suffer a strong rejection both in the academic environment and in the social environment. We must also implement a public policy for the permanence of blacks in universities, which promote social balance, further reducing social and racial inequalities